Using the Kolb's experiential learning cycle to explore the extent of application of one health competencies to solving global health challenges; a tracer study among AFROHUN-Uganda alumni - Tonny Ssekamatte; John Bosco Isunju; Aisha Nalugya; Richard K. Mugambe; Patrick Kalibala; Angella Musewa; Winnie Bikaako; Milly Nattimba; Arnold Tigaiza; Doreen Nakalembe; Jimmy Osuret; Solomon Tsebeni Wafula; et al. (BMC, 2022)
Abstract Background The Africa One Health University Network (AFROHUN) with support from the United States Agency for International Development (USAID), has since 2012 conducted pre and in-service One health (OH) trainings with the objective of improving global health security. These trainings aim to build competencies that, enhance a multidisciplinary approach to solving global health challenges. Despite the investment in OH trainings, there is limited documentation of the extent of acquisition and application of the OH competencies at workplaces. This tracer study explored the extent of acquisition and application of the OH competencies by the AFROHUN-Uganda alumni. Methods A cross-sectional study was conducted among a random sample of 182 AFROHUN-Uganda alumni of 2013-2018 cohorts. A blended approach of interviewer-administered and self-administered questionnaires was used. Virtual platforms such as Zoom, Microsoft teams, and Skype, and phone interviews were used to collect data when face-to-face interactions with alumni were not possible. Data were collected electronically, either through a link or with the aid of the KoboCollect mobile application, pre-installed on android enabled devices, and analysed using STATA14.0. Results The majority of respondents, 78.6% (143/182) had jobs that required application of OH knowledge and skills, 95.6% (174/182) had learned employable skills from OH activities and 89.6% (163/182) had applied such skills when searching for employment. About 21.7% (34/180) to a very high extent required OH field-specific theoretical knowledge at their workplaces, 27.4% (43/80) to a very high extent required OH field-specific practical knowledge/skills, 42.7% (67/180) to a high extent required a change in attitude and perceptions towards working with people from different disciplines, 49.0% (77/180) required collaboration and networking skills, and more than half, 51.0% (80/180) required team building skills. Conclusions The majority of OH alumni to a very high extent acquired and applied OH competences such as teamwork, effective communication, community entry and engagement, report writing and problem-solving skills. This study revealed the significant contribution of the AFROHUN Uganda OH activities towards supportive work environments, and highlights areas of improvement such as supporting the trainees to acquire people-management skills, innovation, and an entrepreneurial mind set.